Astrogliosis in juvenile non-human primates 2 years after infant anaesthesia exposure. (September 2021) - Neudecker, Viola; Perez-Zoghbi, Jose F.; Martin, Lauren D.; Dissen, Gregory A.; Grafe, Marjorie R.; Brambrink, Ansgar M.
Abstract: Background: Infant anaesthesia causes acute brain cell apoptosis, and later in life cognitive deficits and behavioural alterations, in non-human primates (NHPs). Various brain injuries and neurodegenerative conditions are characterised by chronic astrocyte activation (astrogliosis). Glial fibrillary acidic protein (GFAP), an astrocyte-specific protein, increases during astrogliosis and remains elevated after an injury. Whether infant anaesthesia is associated with a sustained increase in GFAP is unknown. We hypothesised that GFAP is increased in specific brain areas of NHPs 2 yr after infant anaesthesia, consistent with prior injury. Methods: Eight 6-day-old NHPs per group were exposed to 5 h isoflurane once (1×) or three times (3×), or to room air as a control (Ctr). Two years after exposure, their brains were assessed for GFAP density changes in the primary visual cortex (V1), perirhinal cortex (PRC), hippocampal subiculum, amygdala, and orbitofrontal cortex (OFC). We also assessed concomitant microglia activation and hippocampal neurogenesis. Results: Compared with controls, GFAP densities in V1 were increased in exposed groups (Ctr: 0.208 [0.085–0.427], 1×: 0.313 [0.108–0.533], 3×: 0.389 [0.262–0.652]), whereas the density of activated microglia was unchanged. In addition, GFAP densities were increased in the 3× group in the PRC and the subiculum, and in both exposure groups in the amygdala, but there was no increase in the OFC. There were no differences in hippocampal neurogenesis among groups. Conclusions: Two years after infant anaesthesia, NHPs show increased GFAP without concomitant microglia activation in specific brain areas. These long-lasting structural changes in the brain caused by infant anaesthesia exposure may be associated with functional alterations at this age.